Application of feedback‐controlled bolus plus infusion (FC‐B/I) method for quantitative PET imaging of dopamine transporters with [18F]β‐CFT‐FE in conscious monkey brain. Issue 1 (31st October 2012) - Harada, Norihiro; Ohba, Hiroyuki; Kakiuchi, Takeharu; Tsukada, Hideo
Abstract The competitive inhibition of dopamine transporters (DAT) with cocaine, a specific DAT inhibitor, was evaluated with a feedback‐controlled bolus plus infusion (FC‐B/I) method using animal positron emission tomography (PET) in the living brain of conscious monkey. 2β‐Carbomethoxy‐3β‐(4‐fluorophenyl)‐8‐(2‐[18F]fluoroethyl) nortropane ([18F]β‐CFT‐FE; Harada et al. [2004] Synapse 54:37–45) was used for this study because it provided specific, fast, and reversible kinetic properties to DAT in the striatum. In FC‐B/I method, the real‐time image reconstruction was started just after intravenous bolus injection of [18F]β‐CFT‐FE to generate a time‐activity curve in the striatum, and the infusion rate was adjusted to achieve an equilibrium state of the striatal radioactivity concentrations by means of a feedback‐control algorithm. The first equilibrium state in the brain was reached within 20 min after the infusion start. Intravenous administration of cocaine at the doses of 0.02, 0.1, and 0.5 mg/kg shifted the equilibrium radioactivity level to the second equilibrium state in a dose‐dependent manner, while no significant alterations was observed in the cerebellum. The present results demonstrated that the combined use of FC‐B/I method and PET probe with fast kinetics like [18F]β‐CFT‐FE could be useful to assess the occupancy of drugs in the living brain with PET. Synapse, 2013. © 2012 Wiley Periodicals, Inc.